A study of Consumer Attitude in Predicting the Purchase behavior towards green Products - Pathak, Shipra; Aggarwal, Shalini; Singh, Satinder Pal (The journal of contemporary issues in business and government, 2021)
One of the indicators which points toward the inclination of consumers for buying green products is the amount of literature which can be seen all around, it has increased manifold. Attitudes of consumers and their perception are closely related, attitudes get heavily influenced by the perceptions a buyer has towards anything. Major influencers of perceptions range from information in media, both electronic and print not excluding social media. Another influencer is peers and they play key role in it. This research intends to investigate as to how consumer attitudes can be utilized to predict consumer behavior towards buying green products. The available data and its consequent analysis points towards an heavy impact of awareness in the buyers towards buying green products. Its beyond reasonable doubt to conclude that the awareness amongst consumers has shaped their perception and thus has altered their buying behavior. The marketers will be largely benefited from further research in such field. The research intended to identify newer areas of influence will lead to major benefits to marketers.